Implementasi pembelajaran diferensiasi dalam Mendukung Pendidikan Inklusif dan SDGs 4 di Sekolah Dasar - Nabila Nasywa; Sakira Azzura Caniago; Dea Febria Br Ketaren; Nisya Sazwana Nasution; Alya Nurmaini Hutasuhut; Asna Istikmalatul Muktamaroh (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to examine the implementation of a differentiated curriculum in supporting inclusive education to achieve the Sustainable Development Goals (SDG 4) in elementary schools. The method used is a qualitatif library research by analyzing various scientific sources such as journals, books, and relevant educational policy documents. The results show that a differentiated curriculum can accommodate diverse student needs through adjustments in content, process, product, and learning environment. This approach contributes to creating more inclusive, adaptive, and student-centered learning. However, its implementation still faces several challenges, including limited teacher understanding, lack of training, and inadequate supporting facilities. Therefore, improving teacher competence, strengthening policy support, and enhancing collaboration among schools, parents, and stakeholders are necessary to achieve quality and sustainable inclusive education.